Where some young people find themselves: Compelling reasons for studying the lives of early school leavers - Marshall, Brian (Curtin University, 2014)
This thesis reflects upon and soberly describes lived situations of young people who voluntarily participated. I come to two points, one is enduring, about what we as educators and researchers can do to ease and sustain re-entry of early school leavers into educational purpose, the other is about transforming conditions of compulsory education that are palatable for them. I uncover a possible transforming moment of conversion that offers an educationally different space for young people.